Understanding the concept of place value: A teaching strategy (Edma 0-6: Educación Matemática en la Infancia, 2017)
This paper reports a study that proposes an alternative teaching strategy to cope with and eventually overcome some difficulties presented by second graders (ages 5-7) at two public Elementary schools in Bogota (Colombia). Based on the analysis of the classroom contexts in both groups and on a literary review on the field, a teaching unit, founded on the Teaching for Understanding framework, was designed, implemented and evaluated. This strategy intended to enhance students’ understanding of the concept of place value. This was a qualitative-descriptive study framed within the Action-Research design. The findings show that students made progress in understanding the concept of place value through the activities proposed in the teaching unit.
Keywords: Elementary school mathematics; Place value; Teaching strategy; Teaching for understanding